Kino Bliskiego Wschodu na polskich ekranach - Fortuna Jr., Grzegorz (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
In the article Middle Eastern Cinema on Polish Screens Grzegorz Fortuna Jr. analyzes the presence of films from the Middle East in Polish cinemas in 2002–2022. The author takes into account major productions from all Middle Eastern countries that have appeared on Polish screens in the last twenty years. The aim of the article is to check to what extent film criticism and research interest in cinematography in this area translates into the actual box office success of individual titles and what factors determined the possible success of Middle Eastern films in Polish cinemas. The author primarily uses Andrew Higson’s theory and distribution research methods, focusing primarily on box office results. The article also aims to check the extent to which the digital revolution has contributed to the popularity of films from the Middle East.